Patient Cross-Border Mobility: New Findings and Implications in Spanish Regions - Carla Blázquez-Fernández; David Cantarero-Prieto; Marta Pascual-Sáez (Economics & Sociology)
Spain has a National Health Service with a mixed public-private funded system. In the last decades, a huge effort has gone into reducing barriers to patient migration. We estimate a panel data based on a gravity model of migration since the process of health care decentralization has been completed in Spain. Our empirical results show that income is one of the most important drivers in explaining mobility as well as supply variables. Individual characteristics are not among the main factors for mobility. Besides, it is demonstrated there is a quality-driven mobility in Spain. However, there was no significant difference in the influence on patients’ mobility between those living in the North of the country and the Mediterranean regions. The empirical results also suggest that current regional health policies in Spain, that explain patients’ mobility, should be associated with greater funding system.